1962
DOI: 10.1021/jm01240a015
|View full text |Cite
|
Sign up to set email alerts
|

Derivatives of 6-Aminopenicillanic Acid. III. Reactions with N-Substituted Phthalamic Acids

Abstract: A number of new and previously described N-substituted phthalamic acids were used for the N-acylation of 6-aminopenicillanic acid (6-APA). The new 6-APA derivatives thus produced were isolated as sodium or potassium salts. The condensation of phthalamic acid with 6-APA failed to yield the expected product. It was found that both N-carbethoxyphthalamic acid and N-carbethoxyphthalimide afforded the same derivative, namely, 6-phthalimidopenicillanic acid. The antimicrobial activity and penicillinase resistance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

1964
1964
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Brine refers to a saturated aqueous solution of sodium chloride. Compounds 6 , 6 - d 1 , and 6 -d 2 ,4e 7 , 8 , 10 , 11 , 2-bromo- N , N -diiospropylbenzamide, 2-bromo- N , N -isopropylbenzamide, and N -isopropylphthalimide ( 12 ) were prepared according to previously published procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Brine refers to a saturated aqueous solution of sodium chloride. Compounds 6 , 6 - d 1 , and 6 -d 2 ,4e 7 , 8 , 10 , 11 , 2-bromo- N , N -diiospropylbenzamide, 2-bromo- N , N -isopropylbenzamide, and N -isopropylphthalimide ( 12 ) were prepared according to previously published procedures.…”
Section: Methodsmentioning
confidence: 99%
“…All of the described NH signals disappear after a D 2 O shake. 13 C NMR of compound 10 also showed four different carbonyl functions. 1 H and 13 C NMR spectra of compound 11 were in accordance with open β-lactam ring and showed no signals corresponding to phthaloyl moiety, suggesting successful dephthaloylation and formation of free NH 2 group, found at 2.00 ppm as a broad singlet.…”
Section: Methodsmentioning
confidence: 95%
“…Namely, thiazolidine NH of compound 9 appears as a characteristic doublet of doublets at 3.84 ppm split by a neighboring thiazolidine C 2 -H and C 4 -H groups with coupling constants of J=8.1 and 13.3 Hz, respectively. 1 H and 13 C NMR of compound 10 showed that both phthalimido and β-lactam rings were opened: new thiazolidine NH appeared as a corresponding doublet of doublets at 3.91 ppm while CONH from phthalimido ring opening appeared as a doublet at 8.38 ppm. Hydrazide NH groups were found as singlets at 9.21 and 9.59 ppm.…”
Section: Methodsmentioning
confidence: 99%
“…While we demonstrated this formal transfer of a protecting phthaloyl entity from one amino group to another in a single system, it may be of use in others involving selective modification of unsymmetrical a,w-diamines such as lysine esters 4 or spermidine, 5 and in purpurosamine 6a and other diaminosugars. 6b-d o- benzoic acid (4) [7][8][9] was converted into the mixed anhydride 5 7 , which on reaction with the amine 1 afforded the diamidophthalimide 6 (Scheme 1). Treatment of this with hydrazine hydrate at -15°C gave the amidohydrazide 7, which was not isolated but reacted with aqueous methanolic hydrochloric acid at 20°C to afford the amine salt (3•HCl).…”
mentioning
confidence: 99%
“…o-(N,N-Diisopropylcarbamoyl)benzoic acid, [7][8][9] in a similar series of reactions, was converted into the mixed anhydride 12 and thence into the diamidophthalimide 13 (Scheme 3). Unlike 6, 13 did not cyclise to the bisphthalimide 8 with aqueous methanolic hydrochloric acid, but did when toluene-p-sulfonic acid in refluxing acetic acid was used.…”
mentioning
confidence: 99%